2008
DOI: 10.1302/0301-620x.90b7.20674
|View full text |Cite
|
Sign up to set email alerts
|

Safety of external fixation during postoperative chemotherapy

Abstract: We studied the safety of external fixation during post-operative chemotherapy in 28 patients who had undergone distraction osteogenesis (17, group A) or vascularised fibular grafting (11, group B) after resection of a tumour. Four cycles of multi-agent post-operative chemotherapy were administered over a mean period of 14 weeks (6 to 27). The mean duration of external fixation for all patients was 350 days (91 to 828). In total 204 wires and 240 half pins were used. During the period of post-operative chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Our caffeine-potentiated chemotherapy protocol (the K2 regimen) appears to have had no hazardous effect on bone regeneration by distraction osteogenesis [34]. Although we have previously shown that chemotherapy decreases regional blood flow to the tumor area, it can be maintained within the normal range or even higher with distraction osteogenesis [35].…”
Section: Discussionmentioning
confidence: 86%
“…Our caffeine-potentiated chemotherapy protocol (the K2 regimen) appears to have had no hazardous effect on bone regeneration by distraction osteogenesis [34]. Although we have previously shown that chemotherapy decreases regional blood flow to the tumor area, it can be maintained within the normal range or even higher with distraction osteogenesis [35].…”
Section: Discussionmentioning
confidence: 86%
“…The most important factor influencing the duration of treatment is patient age, rather than chemotherapeutic agents. Tsuchiya et al also reported that there was no significant difference in the duration of fixation or rates of healing when patients receiving postoperative chemotherapy were compared with those who did not receive chemotherapy after surgery; thus, they considered that chemotherapy has minimal impact on distraction osteogenesis and does not affect eventual bone healing 11 . We reviewed the duration of distraction and fixation, postoperative chemotherapy and imaging information (X-ray) in our pediatric case at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment of post‐traumatic bone defects with the Ilizarov technique has been reported by many authors 12–15. However, its application to bone defects seen after resections for musculoskeletal tumors has only rarely been reported 9–13, 18. Additional reports are limited to bone defects only after benign tumors 5, 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that bone marrow suppression and immune compromised states caused by chemotherapy will thwart bone regeneration as well as increase the rates of pin site infections. Tsuchiya evaluated the use of external fixators during concurrent chemotherapy and reported 11/17 patients with pin site infections and one case that progressed to osteomyelitis 18. High quality studies of this patient population are difficult because of the heterogeneous soft tissue quality and chemotherapy history and previous radiation exposures any of which may adversely affect outcomes.…”
Section: Discussionmentioning
confidence: 99%